2022
DOI: 10.1038/s42003-022-03789-9
|View full text |Cite
|
Sign up to set email alerts
|

The spike of SARS-CoV-2 promotes metabolic rewiring in hepatocytes

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a multi-organ damage that includes hepatic dysfunction, which has been observed in over 50% of COVID-19 patients. Liver injury in COVID-19 could be attributed to the cytopathic effects, exacerbated immune responses or treatment-associated drug toxicity. Herein we demonstrate that hepatocytes are susceptible to infection in different models: primary hepatocytes derived from humanized angiotensin-converting enzyme-2 mice (hACE2) and primary huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The whole-cell lysate was used to evaluate the levels of ATP using the ATPlite Luminescence Assay System, 300 Assay Kit (catalog no. 6016943; Perkin Elmer, Seer Green, UK), following the manufacturer’s instructions and normalized to total protein levels, as described previously [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The whole-cell lysate was used to evaluate the levels of ATP using the ATPlite Luminescence Assay System, 300 Assay Kit (catalog no. 6016943; Perkin Elmer, Seer Green, UK), following the manufacturer’s instructions and normalized to total protein levels, as described previously [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several recent publications directly correlate infection of hepatocytes with hyperglycaemia[44, 45] . With multiple reports correlating hepatic steatosis with the onset of Type 2 Diabetes Mellitus (T2DM), it can be hypothesized that TB-induced hepatic steatosis might predispose TB patients to T2DM and other metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This, therefore, can, in part, explain the hyperglycaemia observed in COVID-19. Mechanistically, molecular analysis suggests the virus promotes the activity of the key gluconeogenic enzyme, phosphoenolpyruvate kinase (PEPCK) [ 62 ]. PEPCK is a rate-limiting enzyme that is inhibited by insulin whilst stimulated by glucagon and other hormones, including glucocorticoids and catecholamines.…”
Section: Sars-cov-2-induced Glycolytic and Hepatic Gluconeogenic Path...mentioning
confidence: 99%
“…Furthermore, studies have reported increases in lactate dehydrogenase over pyruvate dehydrogenase, further supporting the metabolic shift toward hyperglycolysis [ 67 ]. From a biochemical perspective, favouring hyperglycolytic pathways could ensure the sustainable production of lactate [ 62 ]. Lactate, amongst other metabolic substrates, including alanine and glutamates, are the main precursors for glucose in gluconeogenesis.…”
Section: Sars-cov-2-induced Glycolytic and Hepatic Gluconeogenic Path...mentioning
confidence: 99%